The determinants of the flow of foreign direct investment a measuring analytical study of a sample of developing countries for the period (1996-2020) - Hassan, Omar; Zahir, Abdul Hamid (Humanities Journal of University of Zakho, 2023)
This study aims to measure the determinants of the flow of foreign direct investment to developing countries with upper middle income countries within the income classifications in the World Bank including five countries Mexico, Brazil, Malaysia, Romania and China for the period 1996-2020. In order to identify the most important factors that attract this type of investment and its reluctance in these countries, this study relied on the econometrics method using the Autoregressive Distributed Lag, Deceleration model is related to the Balanced Panel data (Panel-ARDL) in order to estimate the parameters of those specific factors in the short and long term, which are GDP growth rate, political stability, gross capital formation, inflation rate and exchange rate. From the results of the study, it was found that in the short term, there is no significant effect with statistical significance between foreign direct investment and the variables that explain it. As for the results of the estimation in the long term, a positive relationship with a significant effect was found between foreign direct investment with both the rate of GDP growth, political stability and total Capital formation in the study sample countries during the period covered by the study. As for the variables that contributed negatively to the flow of foreign direct investment, they are both the exchange rate variable and the inflation rate. The first had a statistically negative and significant impact, while the second had a negative impact, but not significant f, and based on the results, the GDP growth rate variable was the most influential on the flow of foreign direct investment. In the end, the study suggested that the study countries should continue their steps within the framework of restoring and maintaining economic stability, and preparing a comprehensive and realistic investment plan for all investment opportunities, as well as working to stabilize the political situation, which is one of the important factors in achieving the desired volume of foreign capital inflow in the study countries.